2020
DOI: 10.1101/2020.07.20.20155945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 IgG Antibodies in Utsunomiya City, Greater Tokyo, after first pandemic in 2020 (U-CORONA): a household- and population-based study

Abstract: Background: The number of confirmed cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in Japan are substantially lower in comparison to the US and UK, potentially due to the under-implementation of polymerase chain reaction (PCR) tests. Studies reported that more than half of the SARS-CoV-2 infections are asymptomatic, confirming the importance for conducting seroepidemiological studies. Although the seroepidemiological studies in Japan observed a reported prevalence of 0.10% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 4 publications
1
46
0
Order By: Relevance
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
“…Data from prevalence studies for children and adolescents compared with adults are shown in Figure 4. 7, [32][33][34][35][36][38][39][40][41][42][43][44][45] We did not undertake a meta-analysis of population screening studies given the important differences in the populations, epidemic time points, and methodologies involved.…”
Section: Population Screening Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used data from the “Utsunomiya COVID-19 seROprevalence Neighborhood Association (U-CORONA)” study initiated to assess the seroprevalence of COVID-19 in Utsunomiya City, Japan ( Nawa et al, 2020 ). The survey was conducted from 14 th June 2020 to 5 th July 2020, after the first but before the second wave of outbreak in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, the confirmed cases of COVID-19 remained low as of December 2020 compared with those in Europe or northern America. The low seroprevalence (0.03%-0.40%) of COVID-19 in the general population of Japan was reported in several studies conducted from June to September 2020 (1). However, the prevalence of COVID-19 among healthcare workers in Japan, who are at higher risk for COVID-19 infection (2), is not well characterized.…”
Section: Introductionmentioning
confidence: 99%